Blood metabolite concentrations and postpartum resumption of ovarian cyclicity in sanga cows - Damptey, J.K.; Obese, F.Y.; Aboagye, G.S.; Ayim-Akonor, M.; Ayizanga, R.A. (South African Journal of Animal Sciences, 2014)
An experiment was conducted to investigate the effect of concentrations of certain blood nutrient-sensitive metabolites and the resumption of postpartum ovarian cyclicity in 16 Sanga cows (mean BCS 5). Blood samples were taken from cows from weeks 1 to 13 (90 days) postpartum, processed and the plasma progesterone concentration measured to determine the resumption of postpartum ovarian cyclicity. The cows were classified as having resumed ovarian cyclicity when a plasma progesterone concentration of ≥1.0 ng/mL was recorded for two consecutive weekly samples. Based on the resumption of ovarian activity, cows were classified as early cycling, late cycling or non-cycling. The plasma glucose, cholesterol, total protein, albumin and globulin concentrations recorded were similar in the early cycling, late cycling and non-cycling cows. The mean blood glucose, cholesterol, total protein, albumin and globulin concentrations were 3.60 mmol/L, 2.47 mmol/L, 83.1 g/L, 29.9 g/L and 52.9 g/L, respectively. Plasma urea concentrations in late (6.57 ± 0.17 mmol/L) and non-cycling (6.59 ± 0.17 mmol/L) cows were higher than in the early cycling (5.99 ± 0.17 mmol/L) cows in weeks 1 to 13 postpartum. In addition, the plasma creatinine concentration in the early cycling cows was higher than in late cycling cows (101.8 ± 1.82 versus 94.0 ± 1.99 mmol/L). Cows with higher plasma concentrations of urea and lower creatinine concentrations were at risk of delayed resumption of postpartum ovarian cyclicity. Results suggest poor nutritional status, especially energy deficiency, as a major underlying factor suppressing the postpartum resumption of ovarian cyclicity.
Keywords: Bcs; Creatinine; Cycling cows; Plasma; Postpartum; Urea